Ideological Representation in Turkish Cinema and Turkish Cinema During the AK Party Era - İnce, Selami (Border Crossing, 2025)
Cinema has long been recognized by governments for its societal influence, and Turkey is no exception. During the early years of the Republic, while all fine arts flourished under state protection, cinema did not receive the same level of support. However, Turkish cinema evolved in line with the Republic’s official ideology, emphasizing values such as modernization and secularism. As the government acknowledged cinema’s power, it began directing the industry to align with state interests, promoting a "Western" worldview. Following the rise of the Justice and Development Party (AK Party) in 2002, Turkey underwent a shift toward conservatism, with religious values influencing cultural and social life. This article examines how the AK Party’s conservative and religious agenda has shaped Turkish cinema, focusing on whether the 20 highest-grossing films of the AK Party era contributed to a new cultural hegemony and whether Turkish cinema has become more religiously oriented in this period.